Orchestrating Multi-Agent Knowledge Ecosystems: The Role of Makerspaces - Shi, Jia-Lu; Chen, Guo-Hong (Frontiers in Psychology, 2022)
In the knowledge economy, the process of knowledge sharing and creation for value co-creation frequently emerge in a multi-agent and multi-level system. It's important to consider the roles, functions, and possible interactive knowledge-based activities of key actors for ecological development. Makerspace as an initial stage of incubated platform plays the central and crucial roles of resource orchestrators and platform supporter. Less literature analyses the knowledge ecosystem embedded by makerspaces and considers the interactive process of civil society and natural environment. This study constructs a multi-agent and multi-level knowledge ecosystem from macro, meso, and micro perspective based on Quintuple Helix theory and designs four evolutionary stages of knowledge orchestrating processes. This study finds that the symbiosis, co-evolution, interaction, and orchestration of multiple agents in the knowledge ecosystem should be merged with each other for value co-creation, which helps to take a systematic approach for policymakers, managers, and researchers.